Efficacy of HDAC Inhibitors Belinostat and Panobinostat against Cisplatin-Sensitive and Cisplatin-Resistant Testicular Germ Cell Tumors - Lobo, João (Cancers (Basel), 2020)
SIMPLE SUMMARY: There is a need for novel treatment options for patients with testicular germ cell tumors, especially for those that are resistant to standard chemotherapy, who show poor prognosis. In this work, we test two compounds that inhibit epigenetic enzymes called histone deacetylases—belinostat and panobinostat. We show that these enzymes are expressed at different levels in different germ cell tumor subtypes (seminomas and non-seminomas) and that both drugs are effective in reducing tumor cell viability, by decreasing cell proliferation and increasing cell death. These results are promising and should prompt further works with these compounds, envisioning the improvement of care of germ cell tumor patients. ABSTRACT: Novel treatment options are needed for testicular germ cell tumor (TGCT) patients, particularly important for those showing or developing cisplatin resistance, the major cause of cancer-related deaths. As TGCTs pathobiology is highly related to epigenetic (de)regulation, epidrugs are potentially effective therapies. Hence, we sought to explore, for the first time, the effect of the two most recently FDA-approved HDAC inhibitors (HDACis), belinostat and panobinostat, in (T)GCT cell lines including those resistant to cisplatin. In silico results were validated in 261 patient samples and differential expression of HDACs was also observed across cell lines. Belinostat and panobinostat reduced cell viability in both cisplatin-sensitive cells (NCCIT-P, 2102Ep-P, and NT2-P) and, importantly, also in matched cisplatin-resistant subclones (NCCIT-R, 2102Ep-R, and NT2-R), with IC50s in the low nanomolar range for all cell lines. Treatment of NCCIT-R with both drugs increased acetylation, induced cell cycle arrest, reduced proliferation, decreased Ki67 index, and increased p21, while increasing cell death by apoptosis, with upregulation of cleaved caspase 3. These findings support the effectiveness of HDACis for treating TGCT patients in general, including those developing cisplatin resistance. Future studies should explore them as single or combination agents.